The Relationship of the Length of Time Looking for Oysters Against Pap Smear Results in Women Seeking Oysters in Krueng Tibang, Syiah Kuala District Banda Aceh City - salmiani abdul manaf (Institute of Computer Science (IOCS), 2022)
There are problems with health reproduction wrong. The only one is cancer system reproduction. Group vulnerable women _ against viruses and bacteria gender. Exposed women _ direct with bacteria and viruses like working women _look for oysters in estuary puddles. one effort to detect viruses and bacteria sex is with Pap Smear Examination. Pap Smear examination is wrong; one method of inspection screening cancer cervix is by taking smear cell epithelium the cervix to be checked. The objective study is to know Long Time Relationship Look for Oyster To Pap Smear Results on Woman finder Oysters in Krueng Arrive Subdistrict Syiah Kuala Banda Aceh City. Design Study this is survey research with a Cross-sectional study design that is all woman seeker oysters at Krung Cut, Banda Aceh City. The sample in a study is part of the population which is 50 people. Results study shows a connection between long searching oyster to results Pap smear, proven with results chi-square analysis is obtained p-value = 0.047.